2016
DOI: 10.1209/0295-5075/116/45003
|View full text |Cite
|
Sign up to set email alerts
|

Alfvénic ion temperature gradient activities in a weak magnetic shear plasma

Abstract: We report the first experimental evidence of Alfvénic ion temperature gradient (AITG) modes in HL-2A Ohmic plasmas. A group of oscillations with f = 15 − 40 kHz and n = 3 − 6 is detected by various diagnostics in high-density Ohmic regimes. They appear in the plasmas with peaked density profiles and weak magnetic shear, which indicates that corresponding instabilities are excited by pressure gradients. The time trace of the fluctuation spectrogram can be either a frequency staircase, with different modes excit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
(38 reference statements)
6
14
2
Order By: Relevance
“…This latter consideration enforces our instability identification, since Gene detected the excitation of this AITG mode at n = 6, where n is the toroidal wavenumber, which is reflected in the experimental measurements and numerical simulations documented in Ref. [31]. In the latter reference, AITG has been measured by multiple diagnostics lying in the frequency range 15 − 40 kHz, which is in good agreement with the frequency calculated by our numerical simulations.…”
Section: Linear Spectra Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…This latter consideration enforces our instability identification, since Gene detected the excitation of this AITG mode at n = 6, where n is the toroidal wavenumber, which is reflected in the experimental measurements and numerical simulations documented in Ref. [31]. In the latter reference, AITG has been measured by multiple diagnostics lying in the frequency range 15 − 40 kHz, which is in good agreement with the frequency calculated by our numerical simulations.…”
Section: Linear Spectra Analysissupporting
confidence: 87%
“…It must be noted however, that in Ref. [31], the rational surface q = 1 was present, whereas in the simulations presented here, q = 1.06.…”
Section: Linear Spectra Analysiscontrasting
confidence: 57%
“…This dangerous instability has many properties of the theoretically predicted electromagnetic Alfvén ITG (AITG) [4][5][6], and is consistent with the linear gyrokinetic instability analysis [7]. In contrast with the previous claim of the AITG in an ohmic plasma with T i ≤ 0.75 keV without detectable magnetic fluctuationsb [8], the observed mode, considered as the AITG, is multiscale, has appreciableb, and is driven by thermal ions with T i > 10 keV.…”
supporting
confidence: 82%
“…There are also recent reports of KBMs in experiments which exhibit low negative magnetic shear (Chen et al. 2016, 2018), where it is suggested that the same ion-magnetic-drift effect is responsible for the destabilization at small .…”
Section: Impact Of Average Magnetic Shear and Itgmentioning
confidence: 89%